Estrutura produtiva e distribuição de renda em Mato Grosso : uma análise de insumo-produto - Barbosa, Thiago Vieira (2022)
The present research analyzes the role of the productive structure of Mato Grosso in the income distribution of the state of Mato Grosso, considering the analysis for the period of 2015. The economy of Mato Grosso is marked by a productive structure of a primary character. In a recent period, it is noted that the economy of Mato Grosso has been specializing in essentially primary activities due to its insertion in the national and international scope. Income inequality in Mato Grosso measured through the Gini index showed a reduction in the recent period between 2012 and 2020, going from a level of 0.487 in 2012 to 0.462 in 2020. However, the observed levels of income inequality in the state are still high despite the observed reduction. It starts from the conception that the nature of the productive structure with its characteristics define the process of income generation and distribution through the use of factors. In this sense, studying the productive structure proves to be of fundamental importance to expand the understanding of income distribution observed in the economy of Mato Grosso. In methodological terms, the Input-Output model is used, which allows an analysis based on the composition of the productive structure of an economy. Specifically, a variation of the standard Leontief model, the Leontief-Miyazawa model, was adopted. This model makes it possible to highlight the mutual relationship between the production process, income generation/market size inherent to the use of factors in the production process and the specific form that the income distribution phenomenon assumes given the economy's productive structure. The analysis of the results suggests that the important and dynamic sectors of the economy of Mato Grosso do not have great potential to redistribute income in favor of lower-income families or are explicitly associated with an unfavorable distribution. The results also demonstrate that the economic structure of Mato Grosso does not conform in such a way that the main sectors of the economy are the same that have the ability to circumvent the distributional problem, with the exception of the industrial sector of Manufacture of food products. That is, the sectors that have the greatest potential for reducing income inequality are not in line with the core set of sectors that are most important for the dynamics of the Mato Grosso economy. Furthermore, given the characteristics of Mato Grosso's economy in relation to its external insertion and its public sector, the “natural” course of economic expansion is associated with a regressive distribution of income. Therefore, the productive structure of Mato Grosso, in the absence of intervention, was associated with a deterioration in the distributional framework.